Lung metastases of ameloblastic carcinoma 10 years after primary hemimandibulectomy: A case report (Medical Journal of Indonesia, 2009)
Ameloblastoma is a type of odontogenic tumor and generally considered as a benign tumor. However, less than 2% of ameloblastoma were found to have metastases, mostly to the lung. We reported a case of 46-year-old man presenting with an ameloblastic carcinoma with lung metastases 10 years after the primary tumor was resected and 2 years after chemotherapy. (Med J Indones 2009; 18: 60-3) Keywords: ameloblastoma, chemotherapy, radiation